Penatalaksanaan Polip Nasi dengan Operasi Fungsional Endoskopik Sinus - Erna M. Marbun (Jurnal Kedokteran Meditek, 2018)
Nasal polyps are mucosal lesions of the nasal or paranasal sinuses that can be resulted from a response to inflammatory or infections stimuli. Although the exact etiology of this polyp remains unknown,it can coexist with asthma, aspirin intolerance, ,fungal rhinosinusitis, allergy, cystic fibrosis and ciliary dyskinesia. The main symptoms are nasal obstruction and nasal discharge. Endoscopy has enhanced the diagnosis and management of nasal polyps.The initial approach is medical management. Surgical removal is performed for nonresponders to medical management. Functional Endoscopic sinus surgery (FESS) is nowadays a common and excellent method for the treatment of nasal polyposis. Recurrance rates are higher in patients with asthma, but precise recurrence remain elusiveKeywords : nasal polyposis, FESS